Donor-derived Cell-free DNA Kinetics Post-kidney Transplant Biopsy. Issue 6 (25th May 2021) - Kyeso, Yousuf; Bhalla, Anshul; Smith, Alyssa P.; Jia, Yaqi; Alakhdhair, Safa; Ogir, Stephanie C.; Abuzeineh, Mohammad; Brennan, Daniel C.; Alasfar, Sami
Abstract : Background: Donor-derived cell-free DNA (dd-cfDNA) has generated interest as a biomarker for kidney injury including transplant (KT) rejection. It is possible that the KT biopsy procedure can cause the release of dd-cfDNA, therefore affecting the reliability of this assay in the postbiopsy period. We evaluated the effect of KT biopsy on the kinetics of dd-cfDNA. Methods: We conducted a single-arm prospective study. Samples were collected from 16 adult KT recipients undergoing KT biopsy. All participants had samples drawn within 8 h before the biopsy (prebiopsy), within 20 min (hour 0), 2 h (hour 2), and 24–48 h (hours 24–48) after the biopsy. We evaluated the change in dd-cfDNA from the prebiopsy time point to the following 3 time points after the biopsy. Results: At hour 0 and hour 2, there was a significantly larger log dd-cfDNA mean score compared with the prebiopsy score (least square mean estimate 0.4 [0.17-0.63] and 0.39 [0.09-0.68], respectively). By 24–28 h postbiopsy, there was no significant difference in log dd-cfDNA mean score compared with the prebiopsy score (least square mean estimate −0.21 [−0.6 to 0.19]). Conclusions: Mechanical injury from a KT biopsy can transiently increase circulating dd-cfDNA. The increase resolves by 24–48 h after the biopsy. Providers should wait 48 h postbiopsy to obtain dd-cfDNA levels to establish the correct baseline to be used for monitoring.